Resin tags formation by modified Renewal MI formulations in a carious dentine model - Alkhouri, Nabih; Xia, Wendy; Ashley, Paul; Young, Anne (Frontiers in Oral Health, 2024)
Objectives To determine which components in a new restorative material (Renewal MI) improve its ability to form resin tags within demineralized dentine. Methods Varied components included polylysine (PLS), monocalcium phosphate (MCP), powder to liquid ratio (PLR), 4-methacryloyloxyethyl trimellitate anhydride (4META), and polypropylene glycol dimethacrylate (PPGDMA). Urethane dimethacrylate (UDMA), containing PPGDMA (24 wt%) and 4META (3 wt%), was mixed with glass filler with MCP (8 wt%) and PLS (5 wt%). PLR was 3:1 or 5:1. Reducing MCP and/or PLS to 4 and 2 wt% respectively or fully removing MCP, PLS, 4META or PPGDMA gave 16 formulations in total. Renewal MI, Z250 (with or without Scotchbond Universal adhesive) and Activa were used as commercial comparators. Collagen discs were obtained by totally demineralizing 2 mm thick, human, premolar, coronal dentine discs by immersion in formic acid (4M) for 48 h. The restorative materials were then applied on top (n = 3), before dissolving the collagen in sodium hypochlorite (15%). SEM/EDX was employed to determine resin tags length, composition, and surface coverage. Results Tags were >400, 20 and 200 µm and covered 62, 55 and 39% of the adhesion interface for Renewal MI, Scotchbond and Activa, respectively. With experimental formulations, they were 200 and >400 µm long with high vs. low PLR and composed primarily of polymerized monomers. Percentages of the adhesion interface covered varied between 35 and 84%. Reducing PLS or MCP caused a decline in coverage that was linear with their concentrations. Reducing MCP had lesser effect when PLS or PLR were low. Removal of 4META caused a greater reduction in coverage than PPGDMA removal. Conclusion PLS, MCP, 4META, PPGDMA and low PLR together enhance Renewal MI tags formation in, and thereby sealing of, demineralized dentine.